1973
DOI: 10.1103/physrevb.7.3286
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetoelastic Resonance in Thin Films. II. Application to Nickel

Abstract: In Paper I we presented a formal treatment of ferromagnetoelastic resonance (FMER) in thin films. In the present paper, this method is applied to the calculation of resonance lines of nickel at room temperature and at 25.92 GHz, a K-band frequency. It is shown that the FMER conditions are the following: (i) The film thickness nearly equals an odd-integral number of half-wavelengths of the elastic wave at the ferromagnetic-resonance frequency under the spin-unpinned and traction-free boundary conditions, or und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…It should be pointed out that Suhl's theory does not treat the magnon-phonon interaction selfconsistenly. Selfconsistent calculations were carried out by Kobayashi et al [13]. They showed that the magnetoelasticity can have only an appreciable effect on the FMR linewidth if the excited elastic wave establishes a resonant mode across the film thickness at or near the FMR field.…”
Section: B Phonon Dragmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be pointed out that Suhl's theory does not treat the magnon-phonon interaction selfconsistenly. Selfconsistent calculations were carried out by Kobayashi et al [13]. They showed that the magnetoelasticity can have only an appreciable effect on the FMR linewidth if the excited elastic wave establishes a resonant mode across the film thickness at or near the FMR field.…”
Section: B Phonon Dragmentioning
confidence: 99%
“…This effect was called ferromagnetic elastic resonance (FMER). In Ni, the FMER effect can even result in a split FMR peak, see details in [13]. After an extensive and systematic effort to observe FMER in films of perfect Ni and Ni-Co platelets no convincing results were achieved.…”
Section: B Phonon Dragmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising since Terfenol-D's unique magnetostrictive behavior will not be clearly exhibited in a reflection experiment unless the sample is extremely thin. 4,5 The magnetoelastic properties, however, figure prominently in a microwave transmission experiment. It is the purpose of this article to present calculations of the expected microwave transmission through Terfenol-D and to draw attention to the qualitative features that are due to the large magnetostriction.…”
Section: Introductionmentioning
confidence: 98%
“…This effect is appreciable only if resonant conditions exist for the elastic wave, and the resonant frequency is similar to that of the FMR frequency. Due to the long wave-length of such resonant modes, direct phonon coupling is not a significant contribution to precessional damping [49].…”
Section: Direct Electron and Phonon Couplingmentioning
confidence: 99%